Implementation of Business Intelligence to Analyze Opportunities to Enter the Most Popular Majors at SMKN1 Tanjung Pura - Alviona Marsya; Darmeli Nasution; Rian Farta Wijaya (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The use of information technology in education continues to evolve, including in the analysis of vocational school department selection. This study aims to apply Business Intelligence (BI) to analyze admission opportunities in the most popular departments at SMK Negeri 1 Tanjung Pura. The data used is secondary data from SMK applicants between 2020 and 2024, processed using Tableau software for data visualization. The results indicate that the Motorcycle Engineering and Business department is the most favored choice, while the Accounting department has the fewest applicants. BI implementation enables more accurate and informative data presentation, aiding schools in student admission strategies and providing clearer information for prospective students in choosing a department.